Pengembangan Booklet Materi Pencemaran Lingkungan Berdasarkan Struktur Komunitas Makrozoobentos di Ekosistem Mangrove Pantai Solop Indragiri Hilir - Ariani, Dwi; Sri Wulandari; Suwondo (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to identify the structure of the macrozoobenthos community in the mangrove ecosystem of Solop Beach, Indragiri Hilir and to determine the validity of a booklet developed from the research results for use in the Environmental Pollution topic of Grade X Senior High School Biology. The research was conducted from February to April 2025 in the mangrove area of Solop Beach, Mandah District, Indragiri Hilir Regency, Riau Province. The identification process and analysis of the macrozoobenthos community structure were carried out at the Biology Education Laboratory, Faculty of Teacher Training and Education, Universitas Riau. The methods used were the survey method and belt transect method, which are employed to analyze specific regional conditions. The parameters in this study were divided into primary parameters, namely biological parameters, and supporting parameters, namely physical-chemical parameters. The results of the study showed that a total of 8 species of macrozoobenthos were found in the Solop Beach mangrove ecosystem. The research findings were then integrated into a booklet learning media and validated by two experts for use in Grade X Senior High School Biology learning.